The influence of social media marketing and word of mouth on purchasing decisions for skincare products at Alfamidi - Andryanus, Andryanus; Bahri, Ronny Samsul (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to analyze the influence of social media marketing strategies and Word of Mouth (WoM) on the purchase of skincare products at Alfamidi Retail. The study was conducted in Tangerang City, Banten, from September to November 2024, using a quantitative method. Data were obtained through questionnaires and literature studies, and analyzed using descriptive statistical techniques, validity and reliability tests, and multiple regression analysis. The conclusion of the study shows that Media Social Marketing has good criteria with an average score of 3.40. Purchase decisions showed good results, with multiple regression testing showing that Social Media Marketing and WoM had a significant influence on purchase decisions, with a total contribution of 78%.